Mastering Everyday Life in Ordinary Housing for People with Psychiatric Disabilities - Rosita Brolin; David Brunt; Mikael Rask; Susanne Syrén; Anna Sandgren (Grounded Theory Review: An International Journal, 2016)
The aim of this study was to develop a classic grounded theory about people who have psychiatric disabilities and live in ordinary housing with housing support. Interviews and observations during the interviews were analyzed, and secondary analyses of data from previous studies were performed. The impossible mission in everyday life emerged as the main concern and mastering everyday life as the pattern of behavior through which they deal with this concern. Mastering everyday life can be seen as a process, which involves identifying, organizing, tackling, challenging and boosting. Before the process is started, avoiding is used to deal with the main concern. The community support worker, providing housing support, constitutes an important facilitator during the process, and the continuity of housing support is a prerequisite for the process to succeed. If the process mastering everyday life is interrupted by, for example, changes in housing support, the strategy of avoiding is used.